Exploring Obstacles and Successes: Completeness of Toddler Immunization During the COVID-19 Pandemic - Nur Faida. L (Journal of Health Literacy and Qualitative Research, 2021)
The importance of immunization can be seen from the number of toddlers who die from diseases that can be prevented by vaccination (VPD). This research aims to determine the factors related to the completeness of basic immunization among toddlers aged 12-23 months during the Covid-19 pandemic in Layana Village, Mantikulore District, Palu City. This type of research is an analytical survey method using a cross sectional approach. Determination of the sample in this research was carried out using Proportional Random Sampling. The sample taken was 63 people and used Chi-square test data analysis. The results of this study show that there is no relationship between knowledge and completeness of basic immunization in toddlers with a p-value = 0.211 (p > 0.05), there is no relationship between motivation and completeness of basic immunization in toddlers with a value of, p-value = 1.000 (p > 0.05), and there is no relationship between the role of health workers and completeness of basic immunization for toddlers with p-value = 0.253 (p > 0.05). This research recommends increasing the level of maternal knowledge regarding the completeness of immunization by increasing outreach in each sub-district and providing health education to posyandu cadres so that they can assist health workers in increasing community knowledge regarding immunization.